A prospective phase III, randomized, double‐blind, placebo‐controlled study of brodalumab in patients with moderate‐to‐severe plaque psoriasis. (1st August 2016) - Papp, K.A.; Reich, K.; Paul, C.; Blauvelt, A.; Baran, W.; Bolduc, C.; Toth, D.; Langley, R.G.; Cather, J.; Gottlieb, A.B.; Thaçi, D.; Krueger, J.G.; et al.
Summary: Background: The interleukin‐17 cytokine family plays a central role in psoriasis pathogenesis. Objectives: To evaluate the efficacy and safety of brodalumab, a human anti‐interleukin‐17 receptor antibody, in treating patients with moderate‐to‐severe plaque psoriasis. Methods: In this phase III, double‐blind, placebo‐controlled study (NCT01708590; AMAGINE‐1), adult patients in the U.S.A., Canada and Europe were randomized to brodalumab (140 or 210 mg) or placebo every 2 weeks (Q2W), with an additional dose at week 1, for a 12‐week induction phase. At week 12, patients receiving brodalumab who achieved static Physician's Global Assessment 0 or 1 (sPGA success) were rerandomized to the placebo or induction dose. After week 16, patients with sPGA ≥ 3 were re‐treated with the induction dose. After ≥ 12 weeks of retreatment, patients with sPGA 2 for ≥ 4 weeks or sPGA ≥ 3 were rescued with brodalumab 210 mg Q2W. At week 12, patients randomized to brodalumab with sPGA ≥ 2 or placebo received brodalumab 210 mg Q2W. Coprimary end points were the percentage of patients with ≥ 75% improvement in Psoriasis Area and Severity Index score (PASI 75) and sPGA success at week 12. Results: There were 661 patients randomized: 220 placebo, 219 brodalumab 140 mg and 222 brodalumab 210 mg. At week 12, 60% (140 mg) and 83% (210 mg) vs. 3% (placebo) achieved PASI 75, and 54% (140 mg) and 76% (210 mg) vs. 1% (placebo) achieved sPGA success. The safety profile was considered acceptable. Conclusions: Brodalumab therapy resulted in significant clinical benefit and an acceptable safety profile in patients with moderate‐to‐severe plaque psoriasis.